PERAN ARTIFICIAL INTELLIGENCE DALAM MANAJEMEN PEMBELAJARAN AKHLAKUL KARIMAH DI PONDOK PESANTREN MODERN NURUL IKHLAS - Gusti Arizona, Indriani (Pendidikan Dasar dan Manajemen Pendidikan, 2025)
The rapid development of digital technology in the era of the Fourth Industrial Revolution has brought changes in various areas of life, including Islamic education in Islamic boarding schools. One form of influential technological innovation is the application of Artificial Intelligence (AI) in management and learning systems. This article aims to analyze the role of AI in supporting the management of AK (Akhlakul Karimah) learning at the Nurul Ikhlas Modern Islamic Boarding School. This study uses a qualitative method with a literature review approach. Data was collected from various sources such as journals, books, and research reports relevant to the theme of AI integration and Islamic education. The results of this study indicate that (1) AI plays a role in automating the AK learning management administration process, which is carried out in three stages of learning, namely planning, implementation, and evaluation. This application is carried out by integrating the use of AI platforms such as Chat GPT, Canva, Assemblr Edu, and Quizizz. (2) opens up opportunities for the development of more adaptive Islamic education models. However, the implementation of AI requires careful preparation in terms of IT infrastructure, human resources, and a multidisciplinary collaborative approach. It is concluded that with adequate preparation, AI can make a significant contribution to innovation in Islamic education systems in the digital age. Further research is needed to formulate contextual guidelines for the implementation of AI in Islamic education settings.